Sicilian Sulphur and Mafia: Resources, Working Conditions and the Practice of Violence - Carlo Ciccarelli; Alberto Dalmazzo; Tiziano Razzolini (Institute of Labor Economics (IZA), 2021)
This paper reconsiders the nexus between the abundance of resources and the origins of Sicilian mafia by exploiting a new set of historical data on the Sicilian sulphur industry in the late 19th century, obtained from official reports of the Royal Corps of Mining Engineers at the municipal level. We find that the impact of local production on mafia was smaller -or nil- in the areas richest in sulphur. We also find that mechanization in the extraction process was associated with lower incidence of mafia. Taken together, our findings suggest that larger lodes encouraged better and more orderly working conditions for the miners, possibly reducing physical and psychic strain and, consequently, inclination to violence.
Keywords: H75; J28; K42; 330; Mafia; sulphur; working conditions